Heat treatment method for improving intergranular corrosion resistance of nickel-iron-based high-temperature alloy and application

Through the two-step solid solution treatment method, the C element segregation and control carbide precipitation are eliminated, and the intergranular corrosion resistance of nickel-iron-based high-temperature alloys is improved, and the grain boundary depletion problem under high carbon content is solved, ensuring that the alloy is in a high temperature environment. Mechanical properties and corrosion resistance.

CN119320915APending Publication Date: 2025-01-17CHINA HUANENG GRP CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411446775.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Nickel-iron-based high-temperature alloys are prone to depletion of Cr near grain boundaries under high carbon content, resulting in a decrease in intergranular corrosion resistance and affecting their mechanical strength in high temperature environments.

Method used

Using a two-step solid solution treatment method, first perform the first solid solution treatment above the MC type carbide resolution temperature to eliminate element C segregation and control the appropriate grain size, and then the MC type carbide and M23C6 type carbide The second solid solution treatment is carried out within the precipitation temperature range to promote the precipitation of nano-scale MC-type carbides at the grain boundaries and inhibit the precipitation of M23C6-type carbides.

Benefits of technology

It significantly improves the intergranular corrosion resistance of nickel-iron-based high-temperature alloys, while maintaining their mechanical properties. It is suitable for ultra-high temperature environments above 650℃, and meets the material needs of the new generation of ultra-supercritical coal-fired units.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320915A_ABST
    Figure CN119320915A_ABST
Patent Text Reader

Abstract

The invention relates to a heat treatment method for improving intergranular corrosion resistance of a ferronickel-based high-temperature alloy and application, and belongs to the technical field of high-temperature alloy heat treatment, the heat treatment method comprises the following steps: carrying out first solution treatment on the ferronickel-based high-temperature alloy, and controlling the temperature of the first solution treatment to be higher than the re-dissolution temperature of MC type carbide; and carrying out secondary solution treatment on the ferronickel-based high-temperature alloy subjected to the primary solution treatment, wherein the temperature of the secondary solution treatment is controlled between the precipitation temperature of the MC type carbide and the precipitation temperature of the M23C6 type carbide. According to the step of carrying out first-time solution treatment on the ferronickel-based high-temperature alloy, the ferronickel-based high-temperature alloy is machined into a rolled alloy sample, the heat preservation time is determined according to the maximum section thickness t of the sample, the heat preservation time is (90 + t * (0.3-0.5)) min, and water cooling is carried out to the room temperature. The intergranular corrosion resistance of the nickel-iron-based high-temperature alloy can be improved while the mechanical property of the nickel-iron-based high-temperature alloy is guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of heat treatment of high-temperature alloys, and specifically relates to a heat treatment method for improving the intergranular corrosion resistance of nickel-iron-based high-temperature alloys and an application thereof. Background Art

[0002] Nickel-iron-based superalloys are a type of superalloys that use γ′ (Ni3Al) phase strengthening as the main strengthening method. They have good high-temperature strength, fatigue performance, and high-temperature oxidation resistance, and can work in high-temperature environments above 600°C for a long time. At the same time, compared with nickel-based superalloys and cobalt-based superalloys, nickel-iron-based superalloys have a higher cost-effectiveness advantage, becoming the most promising material for key heat channel components of the new generation of ultra-supercritical coal-fired units.

[0003] In order to ensure the high temperature strength of nickel-iron-based high temperature alloys, an appropriate amount of C needs to be added to the material to combine with Cr, Nb, Ti and other elements to form M at the grain boundary. 23 C6 carbides pin grain boundaries, so the C content is required to be no less than 0.03% and can be as high as 0.1%. 23 When C6 carbides precipitate, it is easy to cause the depletion of Cr near the grain boundary, which reduces the intergranular corrosion resistance of the alloy. The intergranular corrosion resistance of the alloy is a key material property. Intergranular corrosion refers to the corrosion that extends inward along the interface between metal grains. This corrosion will destroy the bonding between grains and greatly reduce the mechanical strength of the metal. Therefore, how to improve the intergranular corrosion resistance of high-carbon nickel-iron-based high-temperature alloys is imminent. Summary of the invention

[0004] The purpose of the present invention is to provide a heat treatment method and application for improving the intergranular corrosion resistance of nickel-iron-based high-temperature alloys in order to solve the problems in the above-mentioned prior art, thereby improving the intergranular corrosion resistance of nickel-iron-based high-temperature alloys while ensuring the mechanical properties of the alloys.

[0005] In order to achieve the above object, the present invention has the following technical solutions:

[0006] In a first aspect, an embodiment of the present invention provides a heat treatment method for improving the intergranular corrosion resistance of a nickel-iron-based high-temperature alloy, comprising:

[0007] The nickel-iron-based high-temperature alloy is subjected to a first solid solution treatment, and the temperature of the first solid solution treatment is controlled to be above the dissolution temperature of MC-type carbides;

[0008] The nickel-iron-based high-temperature alloy after the first solution treatment is subjected to a second solution treatment. The temperature of the second solution treatment is controlled between the precipitation temperature of MC type carbides and the precipitation temperature of M 23 Between the precipitation temperatures of C6 type carbides.

[0009] As a preferred solution, the temperature of the first solution treatment is controlled at 1040°C to 1100°C.

[0010] As a preferred solution, in the step of performing the first solution treatment on the nickel-based superalloy, the holding time is determined according to the maximum cross-sectional thickness t of the nickel-based superalloy sample, and the holding time is (90 + t×(0.3 - 0.5)) min, and then water-cooled to room temperature.

[0011] As a preferred solution, the temperature of the second solution treatment is controlled at 980°C to 1020°C.

[0012] As a preferred solution, in the step of performing the second solution treatment on the nickel-based superalloy after the first solution treatment, the holding time is 30 min to 60 min, and then water-cooled to room temperature.

[0013] As a preferred solution, the nickel-based superalloy is made into a rolled sample.

[0014] As a preferred solution, the maximum cross-sectional thickness t of the nickel-based superalloy sample is 70 mm to 100 mm.

[0015] As a preferred solution, by weight percentage, the chemical composition of the nickel-based superalloy includes:

[0016] 0.03% ≤ C ≤ 0.1%, 0 < B ≤ 0.005%, 14% ≤ Cr ≤ 18%, 0 ≤ Co ≤ 3%, 0.5% ≤ Mo ≤ 1%, 0 ≤ W ≤ 1%, 0 ≤ Nb ≤ 1%, 0 ≤ Si ≤ 0.5%, 1 ≤ Al ≤ 2.5%, 1.5% ≤ Ti ≤ 3%, 40% ≤ Fe ≤ 45%, and the balance is Ni.

[0017] In a second aspect, the embodiments of the present invention also provide a nickel-based superalloy sample prepared by a heat treatment method for improving the intergranular corrosion resistance of a nickel-based superalloy. The average grain size of the nickel-based superalloy sample is 170 μm to 192 μm, and the yield strength at 700°C is not less than 300 MPa; the intergranular corrosion is evaluated according to Method A in GB / T 15260-2016 "Corrosion of Metals and Alloys - Intergranular Corrosion Test Methods for Nickel Alloys", and the intergranular corrosion rate does not exceed 0.5 mm / y.

[0018] In a third aspect, the embodiments of the present invention also provide an application of a heat treatment method for improving the intergranular corrosion resistance of a nickel-based superalloy in the production of nickel-based superalloy plates, bars, tubes and forgings for 650°C class ultra-supercritical coal-fired power generation units.

[0019] Compared with the prior art, the present invention has at least the following beneficial effects:

[0020] The heat treatment method proposed in the present invention first performs a first solid solution treatment on the nickel-iron-based high-temperature alloy, and the temperature of the first solid solution treatment is controlled to be above the dissolution temperature of MC-type carbides. The first solid solution treatment can eliminate the segregation of the C element and fully dissolve the MC-type carbides. At the same time, a suitable grain size can be obtained, and the number of grain boundaries can be reduced, laying a foundation for the subsequent control of the precipitation of grain boundary carbides. After that, the nickel-iron-based high-temperature alloy after the first solid solution treatment is subjected to a second solid solution treatment, and the temperature of the second solid solution treatment is controlled to be above the precipitation temperature of MC-type carbides and above the precipitation temperature of MC-type carbides. 23 The precipitation temperature of C6 type carbide is between 100℃ and 100℃, and the size and precipitation amount of MC type carbide are controlled by the second solution treatment, which promotes the precipitation of nano-scale MC type carbide preferentially at the grain boundary, thereby inhibiting the precipitation of M 23 The precipitation of C6 at the grain boundary and the uniformity of the grain size are further improved. The present invention can improve the intergranular corrosion resistance of the nickel-iron-based high-temperature alloy while ensuring its mechanical properties, making the alloy particularly suitable for ultra-high temperature steam environments above 650°C and meeting the material requirements of key heat channel components of a new generation of ultra-supercritical coal-fired units. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0022] Figure 1a This is a metallographic picture of the nickel-iron-based high-temperature alloy tube after heat treatment in Example 1 of the present invention;

[0023] Figure 1b This is a scanning electron microscope image of the nickel-iron-based high-temperature alloy tube after heat treatment in Example 1 of the present invention;

[0024] Figure 2 This is a metallographic picture of the nickel-iron-based high-temperature alloy tube after heat treatment in Example 2 of the present invention;

[0025] Figure 3 This is a metallographic picture of the nickel-iron-based high-temperature alloy tube after heat treatment in Example 3 of the present invention.

[0026] Figure 4a This is a metallographic picture of the nickel-iron-based high-temperature alloy pipe after conventional heat treatment in Comparative Example 1;

[0027] Figure 4b This is a scanning electron microscope image of the nickel-iron-based high-temperature alloy tube after conventional heat treatment in Comparative Example 1;

[0028] Figure 5This is a metallographic picture of the nickel-iron based high temperature alloy tube after high temperature solution treatment in comparative example 2. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, ordinary technicians in this field can also obtain other embodiments without making creative work.

[0030] The following examples are provided to better explain the present invention, are not limited to the best mode, and are not intended to limit the content and scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the enlightenment of the present invention or by combining the features of the present invention with other prior arts, all falls within the protection scope of the present invention. If no specific experimental steps or conditions are indicated in the examples, the operation or conditions of the conventional experimental steps described in the literature in this field can be carried out. If the manufacturer is not indicated for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0031] The embodiment of the present invention provides a heat treatment method for improving the intergranular corrosion resistance of nickel-iron-based high-temperature alloy, comprising:

[0032] The nickel-iron-based high-temperature alloy is subjected to a first solid solution treatment, and the temperature of the first solid solution treatment is controlled to be above the dissolution temperature of MC-type carbides;

[0033] The nickel-iron-based high-temperature alloy after the first solution treatment is subjected to a second solution treatment. The temperature of the second solution treatment is controlled between the precipitation temperature of MC type carbides and the precipitation temperature of M 23 The precipitation temperature of C6 type carbide is between.

[0034] In an embodiment of the present invention, the nickel-iron-based high-temperature alloy is processed into a rolled alloy sample. By adopting a heat treatment method combining high-temperature solid solution and low-temperature solid solution to the rolled alloy sample, while improving the intergranular corrosion resistance of the nickel-iron-based high-temperature alloy sample, the mechanical properties of the nickel-iron-based high-temperature alloy are basically not reduced, which is conducive to promotion and application.

[0035] Furthermore, the maximum cross-sectional thickness t of the rolled nickel-iron-based high-temperature alloy sample of the embodiment of the present invention is 70 mm to 100 mm.

[0036] In a possible implementation manner, the nickel-iron-based high-temperature alloy has chemical components, measured by weight percentage, including:

[0037] 0.03% ≤ C ≤ 0.1%, 0 < B ≤ 0.005%, 14% ≤ Cr ≤ 18%, 0 ≤ Co ≤ 3%, 0.5% ≤ Mo ≤ 1%, 0 ≤ W ≤ 1%, 0 ≤ Nb ≤ 1%, 0 ≤ Si ≤ 0.5%, 1 ≤ Al ≤ 2.5%, 1.5% ≤ Ti ≤ 3%, 40% ≤ Fe ≤ 45%, and the balance is Ni.

[0038] The heat treatment method for improving the intergranular corrosion resistance of the nickel-iron-based superalloy in the embodiments of the present invention can be achieved through the following steps:

[0039] S1. Heat the hot-rolled nickel-iron-based superalloy specimen in the furnace to 1040°C to 1100°C, determine the holding time according to the maximum cross-sectional thickness t of the hot-rolled nickel-iron-based superalloy specimen, and the holding time is (90 + t × (0.3 - 0.5)) min, then water-cool to room temperature;

[0040] S2. Heat the hot-rolled nickel-iron-based superalloy specimen processed in step S1 to 980°C to 1020°C, hold for 30 min to 60 min, and then water-cool to room temperature, thus completing the heat treatment for improving the intergranular corrosion resistance of the nickel-iron-based superalloy.

[0041] The nickel-iron-based superalloy specimen prepared by the heat treatment method for improving the intergranular corrosion resistance of the nickel-iron-based superalloy in the embodiments of the present invention has an average grain size of 170 μm to 192 μm, and the yield strength at 700°C is not less than 300 MPa; the intergranular corrosion is evaluated according to method A in GB / T 15260-2016 "Corrosion of metals and alloys - Intergranular corrosion testing of nickel alloys", and the intergranular corrosion rate does not exceed 0.5 mm / y, which is reduced by 33% to 56% compared with the ordinary process.

[0042] Method A in GB / T 15260-2016 "Corrosion of metals and alloys - Intergranular corrosion testing of nickel alloys", namely the ferric sulfate(III)-sulfuric acid test, is an important method for determining the intergranular corrosion sensitivity of nickel-based alloys.

[0043] Method A is mainly applicable to determining the intergranular corrosion sensitivity of nickel-based alloys in the ferric sulfate(III)-sulfuric acid test solution.

[0044] For nickel-iron-based superalloys with a relatively high C content, C element segregation is likely to occur during the hot working process, and even large MC-type carbides are locally precipitated, which is inherited to the subsequent heat treatment process. In addition, in order to ensure that both the grain boundaries and the grains of the nickel-iron-based superalloy have sufficient strength, a heat treatment method combining solution treatment and aging treatment is often adopted, and a large number of discontinuous M 23C6 type carbide, thereby achieving grain boundary strengthening. The above factors all lead to local Cr deficiency in the alloy, increase the sensitivity to intergranular corrosion, and cause the intergranular corrosion resistance in the sensitized state to be unqualified. The use of high solution temperature or long solution time can improve the material's resistance to intergranular corrosion, but it will cause abnormal growth of grains during the solution process, thereby damaging the mechanical properties. The present invention adopts a two-step progressive solution heat treatment method. The temperature of the first step of the solution treatment is selected to be above the dissolution temperature of MC type carbides to achieve the elimination of C element segregation and sufficient dissolution of MC type carbides; at the same time, a suitable grain size can be obtained, and the number of grain boundaries can be reduced, laying the foundation for the subsequent control of the precipitation of grain boundary carbides; the temperature of the second step of the solution treatment is selected to be between the precipitation temperature of MC type carbides and M 23 C6 precipitation temperature, control the size and precipitation amount of MC carbides, promote the precipitation of nano-scale MC carbides preferentially at the grain boundaries, thereby inhibiting the precipitation of M 23 C6 precipitates at the grain boundaries; at the same time, the uniformity of grain size is further improved.

[0045] MC type carbide and M 23 C6 carbides are significantly different in many aspects. In terms of composition and structure, MC carbides are mainly composed of molybdenum (Mo) and carbon (C), and sometimes also contain iron, forming a complex cubic lattice structure. 23 C6 carbide is mainly chromium carbide, sometimes written as Cr 23 C6, but elements such as iron and molybdenum often partially replace chromium, so it is also written as (Cr,Fe) 23 C6 or (Cr,Fe,Mo) 23 C6.M 23 C6 has a complex face-centered cubic structure, with 92 metal atoms and 24 carbon atoms in each unit cell. Usually, MC carbides are formed at high temperatures, especially in alloys such as high-speed steel. They have fine granular or rod-like structures and are dispersed in the matrix. 23 C6 carbides are mainly formed in austenitic stainless steels that do not contain strong carbide-forming elements such as titanium and niobium. The precipitation temperature range is 400℃ to 950℃, and the precipitation kinetics depends on the chemical composition of the steel and the previous processing experience. MC carbides are distributed in the matrix in granular or rod-like form, which effectively enhances the hardness and wear resistance of the steel. Steels with high molybdenum (Mo) content can produce a secondary hardening effect, refine the grains, and improve thermal stability. 23 C6 carbides are mainly distributed at the interface between pearlite and cementite, and have little effect on the mechanical properties of the material. 23 C6 carbides may partially transform into other types of carbides, such as NbC. MC carbides are mainly distributed at grain boundaries in materials such as cast iron, and have an important influence on the mechanical properties of the material.23 C6 carbides mainly affect the mechanical properties of materials, especially at high temperatures. 23 C6 carbides have obvious differences in composition, structure, formation conditions, performance effects, and distribution. These differences make them play different roles in different materials science and engineering applications.

[0046] The embodiment of the present invention also proposes an application of the heat treatment method for improving the intergranular corrosion resistance of nickel-iron-based high-temperature alloy in the production of nickel-iron-based high-temperature alloy plates, bars, pipes and forgings for 650°C grade ultra-supercritical coal-fired units.

[0047] The heat treatment method for improving the intergranular corrosion resistance of nickel-iron-based high-temperature alloys in the embodiment of the present invention ensures that the nickel-iron-based high-temperature alloys have good mechanical properties while improving their intergranular corrosion resistance. The proposed two-step progressive solution treatment method is easy to operate, can replace the existing heat treatment process of nickel-iron-based high-temperature alloys, and can be embedded in its production process to save costs.

[0048] The following examples are compared with comparative examples to illustrate the effects of the present invention.

[0049] Example 1

[0050] The hot-rolled nickel-iron-based high-temperature alloy pipe with a wall thickness of 70 mm is made, and the chemical composition by weight percentage is:

[0051] C: 0.08%, B: 0.003%, Cr: 15%, Co: 2%, Mo: 0.8%, W: 0.5%, Nb: 0.5%, Al: 1.9%, Ti: 2.2%, Fe: 40%, and the balance is Ni.

[0052] The hot-rolled nickel-iron-based high-temperature alloy tube was heated to 1040°C in a furnace, kept at this temperature for 125 minutes, and water-cooled to room temperature; then the temperature was raised to 980°C in a furnace, kept at this temperature for 60 minutes, and water-cooled to room temperature.

[0053] like Figure 1a and Figure 1b As shown, the heat-treated pipe was taken and the grain size was measured according to GB / T 6394-2002 "Method for Determination of Average Grain Size of Metals". It can be seen that the pipe has uniform equiaxed grains with an average grain size of 171μm.

[0054] The intergranular corrosion evaluation was carried out according to Method A in GB / T 15260-2016 "Corrosion of Metals and Alloys - Test Method for Intergranular Corrosion of Nickel Alloys", and the intergranular corrosion rate was 0.31 mm / y. The results are shown in Table 1. The high temperature tensile property test was carried out at 700°C, and the results are shown in Table 2.

[0055] Example 2

[0056] The hot-rolled nickel-iron-based high-temperature alloy tube with a wall thickness of 100 mm is made, and the chemical composition by weight percentage is:

[0057] C: 0.1%, B: 0.006%, Cr: 16%, Mo: 1.0%, W: 1.0%, Nb: 0.3%, Al: 1.5%, Ti: 1.8%, Fe: 42%, and the balance is Ni.

[0058] The hot rolled pipe is heated to 1100°C in a furnace, kept at this temperature for 120 minutes, and water cooled to room temperature; then the temperature is raised to 1000°C in a furnace, kept at this temperature for 45 minutes, and then water cooled to room temperature.

[0059] The heat-treated pipe was measured according to GB / T 6394-2002 "Method for Determination of Average Grain Size of Metals". It can be seen that the pipe has uniform equiaxed grains with an average grain size of 189μm (such as Figure 2 The intergranular corrosion evaluation was carried out according to Method A in GB / T 15260-2016 "Corrosion of Metals and Alloys - Test Method for Intergranular Corrosion of Nickel Alloys", and the intergranular corrosion rate was 0.33 mm / y. The results are shown in Table 1. The high temperature tensile property test was carried out at 700°C, and the results are shown in Table 2.

[0060] Example 3

[0061] The hot-rolled nickel-iron-based high-temperature alloy pipe with a wall thickness of 80 mm is made, and the chemical composition by weight percentage is:

[0062] C: 0.05%, B: 0.006%, Cr: 17%, Mo: 0.5%, W: 0.8%, Nb: 0.5%, Al: 1.72%, Ti: 2.1%, Fe: 43%, and the balance is Ni.

[0063] The hot rolled pipe was heated to 1080°C in the furnace, kept at this temperature for 114 minutes, and water cooled to room temperature; then the temperature was raised to 1020°C in the furnace, kept at this temperature for 30 minutes, and water cooled to room temperature.

[0064] The heat-treated pipe was measured according to GB / T 6394-2002 "Method for Determination of Average Grain Size of Metals". It can be seen that the pipe has uniform equiaxed grains with an average grain size of 192μm (such as Figure 3 The intergranular corrosion evaluation was carried out according to Method A in GB / T 15260-2016 "Corrosion of Metals and Alloys - Test Method for Intergranular Corrosion of Nickel Alloys", and the intergranular corrosion rate was 0.36 mm / y. The results are shown in Table 1. The high temperature tensile property test was carried out at 700°C, and the results are shown in Table 2.

[0065] Comparative Example 1

[0066] The same hot-rolled iron-nickel-based high-temperature alloy tube as in Example 1 was used for conventional heat treatment, wherein the hot-rolled tube was heated to 1040° C. in a furnace, kept at this temperature for 125 min, and then cooled to room temperature with water;

[0067] Then the temperature was raised to 680°C in the furnace, kept at that temperature for 8 hours and then cooled to room temperature with water.

[0068] like Figure 4a and Figure 4b As shown, the pipe that has undergone conventional heat treatment was taken and the grain size was measured according to GB / T 6394-2002 "Method for Determination of Average Grain Size of Metals". It can be seen that the pipe has uniform equiaxed grains with an average grain size of 83μm.

[0069] The intergranular corrosion evaluation was carried out according to Method A in GB / T 15260-2016 "Corrosion of Metals and Alloys - Test Method for Intergranular Corrosion of Nickel Alloys", and the intergranular corrosion rate was 0.71 mm / y. The results are shown in Table 1. The tensile properties test was carried out at high temperature, and the results are shown in Table 2.

[0070] Comparative Example 2

[0071] The same hot-rolled iron-nickel-based high-temperature alloy tube as in Example 1 was used for high-temperature solution treatment. The hot-rolled tube was heated to 1150° C. in a furnace, kept at this temperature for 125 min, and then water-cooled to room temperature.

[0072] The grain size of the pipes after high temperature solution treatment was measured according to GB / T 6394-2002 "Method for Determination of Average Grain Size of Metals". It can be seen that the grain size of the pipes is uneven, and there are abnormally grown grains, such as Figure 5 The intergranular corrosion evaluation was carried out according to Method A in GB / T 15260-2016 "Corrosion of Metals and Alloys - Test Method for Intergranular Corrosion of Nickel Alloys", and the intergranular corrosion rate was 0.71 mm / y. The results are shown in Table 1. The tensile properties test was carried out at high temperature, and the results are shown in Table 2.

[0073] Table 1 Intergranular corrosion rate of Fe-Ni-based superalloy after heat treatment

[0074]

[0075] Table 2 High temperature mechanical properties of Fe-Ni-based superalloy pipes after heat treatment at 700℃

[0076]

[0077] The heat treatment method for improving the intergranular corrosion resistance of nickel-iron-based high-temperature alloys proposed in the embodiment of the present invention is suitable for producing nickel-iron-based high-temperature alloy plates, bars, pipes and forgings for 650°C grade ultra-supercritical coal-fired units.

[0078] Normally, nickel-iron-based high-temperature alloy plates can be used to manufacture components such as boilers, superheaters, and reheaters of ultra-supercritical coal-fired units. These components need to withstand complex environments of high temperature, high pressure, and corrosion. The high-temperature strength and corrosion resistance of nickel-iron-based high-temperature alloy plates make them an ideal choice. Nickel-iron-based high-temperature alloy bars can be used to manufacture key components in ultra-supercritical coal-fired units, such as rotors, blades, shafts, etc. These components operate under high speed, high temperature, and high pressure environments, and have extremely high requirements for the mechanical properties, heat resistance, and corrosion resistance of the materials. Nickel-iron-based high-temperature alloy pipes are mainly used to transport high-temperature, high-pressure, and corrosive media, such as steam and fuel. In ultra-supercritical coal-fired units, they are used to manufacture boiler pipes, superheater pipes, reheater pipes, etc. Nickel-iron-based high-temperature alloy forgings play an important role in ultra-supercritical coal-fired units. They are used to manufacture key components such as turbine blades, guide vanes, and control rods. These components need to withstand the test of high temperature, high pressure, high speed, and corrosive environments. The excellent performance of nickel-iron-based high-temperature alloy forgings makes them an ideal choice. Nickel-iron-based superalloys can still maintain high strength and hardness at high temperatures, ensuring stable operation of components in high temperature environments. In high temperature environments, nickel-iron-based superalloys can form a dense oxide film to prevent further oxidation and corrosion. Nickel-iron-based superalloys show good corrosion resistance in a variety of corrosive media and can resist erosion by corrosive substances such as acids, alkalis, and salts. Nickel-iron-based superalloys are easy to process and form, and can be made into components of various shapes and specifications through forging, rolling, welding and other processes.

[0079] The embodiments of the present invention can improve the intergranular corrosion resistance of nickel-iron-based high-temperature alloys with high carbon content, and substantially do not reduce the mechanical properties of the nickel-iron-based high-temperature alloy while improving the intergranular corrosion resistance of the nickel-iron-based high-temperature alloy sample.

[0080] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A heat treatment method for improving the intergranular corrosion resistance of nickel-iron-based high-temperature alloy, characterized in that: Comprising: Performing a first solution treatment on the nickel-based superalloy, and controlling the temperature of the first solution treatment above the re-dissolution temperature of MC-type carbides; The nickel-iron-based high-temperature alloy after the first solution treatment is subjected to a second solution treatment. The temperature of the second solution treatment is controlled between the precipitation temperature of MC type carbides and the precipitation temperature of M 23 Between the precipitation temperatures of C6 type carbides.

2. The heat treatment method for improving the intergranular corrosion resistance of nickel-iron-based high-temperature alloy according to claim 1, characterized in that: Controlling the temperature of the first solution treatment at 1040°C to 1100°C.

3. The heat treatment method for improving the intergranular corrosion resistance of nickel-iron-based high-temperature alloy according to claim 1 or 2, characterized in that: For the step of performing the first solution treatment on the nickel-based superalloy, determining the holding time according to the maximum cross-sectional thickness t of the nickel-based superalloy specimen, and the holding time is (90 + t×(0.3 - 0.5)) min, and water-cooling to room temperature.

4. The heat treatment method for improving the intergranular corrosion resistance of nickel-iron-based high-temperature alloy according to claim 1, characterized in that: Controlling the temperature of the second solution treatment at 980°C to 1020°C.

5. The heat treatment method for improving the intergranular corrosion resistance of nickel-iron-based high-temperature alloy according to claim 1 or 4, characterized in that: For the step of performing the second solution treatment on the nickel-based superalloy after the first solution treatment, the holding time is 30 min to 60 min, and water-cooling to room temperature.

6. The heat treatment method for improving the intergranular corrosion resistance of nickel-iron-based high-temperature alloy according to claim 1, characterized in that: Manufacturing the nickel-based superalloy into a rolled specimen.

7. The heat treatment method for improving the intergranular corrosion resistance of nickel-iron-based high-temperature alloy according to claim 1 or 6, characterized in that: The maximum cross-sectional thickness t of the nickel-based superalloy specimen is 70 mm to 100 mm.

8. The heat treatment method for improving the intergranular corrosion resistance of nickel-iron-based high-temperature alloy according to claim 1, characterized in that: The nickel-based superalloy, by weight percentage, has chemical components including: 0.03% ≤ C ≤ 0.1%, 0 < B ≤ 0.005%, 14% ≤ Cr ≤ 18%, 0 ≤ Co ≤ 3%, 0.5% ≤ Mo ≤ 1%, 0 ≤ W ≤ 1%, 0 ≤ Nb ≤ 1%, 0 ≤ Si ≤ 0.5%, 1 ≤ Al ≤ 2.5%, 1.5% ≤ Ti ≤ 3%, 40% ≤ Fe ≤ 45%, and the balance is Ni.

9. A nickel-iron-based high-temperature alloy sample prepared by the heat treatment method for improving the intergranular corrosion resistance of the nickel-iron-based high-temperature alloy according to any one of claims 1 to 8, characterized in that: The average grain size of the nickel-based superalloy specimen is 170 μm to 192 μm, and the yield strength at 700°C is not less than 300 MPa; the intergranular corrosion is evaluated according to Method A in GB / T 15260-2016 "Test Methods for Intergranular Corrosion of Nickel Alloys - Metals and Alloys", and the intergranular corrosion rate does not exceed 0.5 mm / y.

10. Application of a heat treatment method for improving the intergranular corrosion resistance of a nickel-based superalloy according to any one of claims 1 to 8 in the production of nickel-based superalloy plates, bars, tubes and forgings for 650°C class ultra-supercritical coal-fired power generation units.